2015
DOI: 10.1103/physrevc.92.014306
|View full text |Cite
|
Sign up to set email alerts
|

Chiral three-nucleon forces and the evolution of correlations along the oxygen isotopic chain

Abstract: Background: Three-nucleon forces (3NFs) have non trivial implications on the evolution of correlations at extreme proton-neutron asymmetries. Recent ab initio calculations show that leading order chiral interactions are crucial to obtain the correct binding energies and neutron driplines along the O, N, and F chains, Ref.[A. Cipollone, C. Barbieri, P. Navrátil, Phys. Rev. Lett 111, 062501 (2013)].Purpose: Here, we discuss the impact of 3NFs along the oxygen chain for other quantities of interest, such has the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 83 publications
(168 reference statements)
8
142
1
Order By: Relevance
“…The importance of nuclear correlations was established, for example, in the early (e,e p) experiments [6][7][8] from which strong reductions of single particle strength was inferred. While such measurements might have initially been conjectured to be short-range effects, later calculations clearly demonstrated that they must be ascribed almost completely to LRC dynamics [2,9,10]. This is confirmed by (e,e p) observations at small missing energies and large missing momenta [11,12].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The importance of nuclear correlations was established, for example, in the early (e,e p) experiments [6][7][8] from which strong reductions of single particle strength was inferred. While such measurements might have initially been conjectured to be short-range effects, later calculations clearly demonstrated that they must be ascribed almost completely to LRC dynamics [2,9,10]. This is confirmed by (e,e p) observations at small missing energies and large missing momenta [11,12].…”
Section: Introductionsupporting
confidence: 57%
“…In the present paper we report the results of a measurement of the 12 C(e,e pp) 10 Be reaction performed at MAMI in super-parallel kinematics, that is sensitive to the one-body emission channel, and partially suppresses other mechanisms capable to produce two protons in the final state. A silicon detector telescope (SDT) for proton detection has been developed [35] and employed along with two high-resolution magnetic spectrometers of the A1 Collaboration [36] that have been used for detecting the scattered electron and the other proton.…”
Section: Introductionmentioning
confidence: 99%
“…[55,62]. Note that the ADC(3) Self-Consistent Green's Function results [128,159] were obtained for λ = 2.0 fm −1 , but the dependence of energies on λ is very weak. Black bars indicate experimental data [110].…”
Section: Ground-state Calculations For Closed-and Open-shell Nucleimentioning
confidence: 98%
“…In addition to IT-NCSM, CCSD, and Λ-CCSD(T) (cf. 5.4), we also include results from the Self-Consistent Green's Function (SCGF) approach in the ADC(3) scheme [128,159]. The latter are obtained at a slightly different resolution scale λ = 2.0 fm −1 , but the dependence of the ground-state energies on λ is very weak, at least in the range λ = 1.88, .…”
Section: Oxygen Isotopesmentioning
confidence: 99%
See 1 more Smart Citation